A poly(A) addition site and a downstream termination region are required for efficient cessation of transcription by RNA polymerase II in the mouse beta maj-globin gene. - Logan, J (1987)
Sequence elements within the mouse beta maj-globin transcription unit required for efficient termination of transcription by RNA polymerase II have been delineated. To facilitate nascent-chain analysis of termination, the DNA segment in which transcription ceases was introduced into the adenovirus chromosome within its E1A transcription unit. Two beta-globin DNA elements were required to effect efficient termination: an upstream sequence that includes two poly(A) addition signals and a downstream region previously shown to be where RNA synthesis stops. The role of poly(A) addition in termination was established by introduction of several single base pair substitutions into the AATAAA polyadenylylation motifs. These mutations inhibited both polyadenylylation and termination within the beta-globin DNA segment. Therefore, poly(A) addition appears to be a prerequisite for efficient termination.